GEOLOGICAL CHARACTERISTICS OF TEHRAN AQUIFER - Khaksar, Kaveh; Tavassoli, Abolghasem (Águas Subterrâneas, 2002)
The alluvial deposits of Tehran is composed of up to 1100 m and is divided into five parts: The first part (~500 m) has been denominated as first member of Hezardareh Formation and has been formed of hard conglomerate of Upper Pliocene age. This part has many few porosity, high erodibility of pebbles and strongly cementation. The second part (second member of Hezardareh Formation has been composed of ~500 m of incoherent conglomerate and conglomeratic sandstone deposits of Lower Pleistocene age. This member has highly porosity respect to first member and less grade of erodibility. The third horizon (Kahrizak Formation) with 10 to 60 m of thickness contains pebble, gravel and sand. It is Middle Pleistocene in age. The fourth stage (Tehran alluvium) with 50 m of thickness has been formed by stratified gravels of Upper Pleistocene age. In general this Formation is composed of heterogeneous grains and because of having frail cement between pebbles it is permeable and with relatively high mechanical resistance. Tehran alluvium has been the better depository of underground water in the alluvial fan of Tehran region. The fifth part (Holocene stage) with 1-5 m of thickness contains coating pebbles, gravel and fine sediments. It is composed of separated and highly permeable deposits, which its mechanical resistance differs in different part of the region. The thickness of alluvial aquifer is estimated about 300-350 m, which composed of second member of Hezardareh and younger Formation. Much of the groundwater essential to agriculture and human existence emanetes from aquifers in Quaternary sediments of Tehran plain. According to our surveys and data, annually water consumption of Tehran city is about 700 million meter cubic which 20.8% of it discharges from Quaternary deposited sediments.